Argostemma bachmaense (Rubiaceae, Rubioideae, Argostemmateae), a new species from central Vietnam. (17th July 2020) - Van Do, Truong; Zhe, Chen; Yang, Niu
Abstract : Argostemma bachmaense, a new species from central Vietnam, is described and illustrated here. The new species is most similar to A. laoticum and A. vietnamicum but can be distinguished from the latter two by having a well‐developed internode with leaf pairs separately arranged along stem, isophyllous or slightly anisophyllous leaves, an oblanceolate to spatulate lamina with attenuate base and lateral veins with 4–5 pairs prominent on abaxially, a terminal, solitary flower, an absent bract, narrowly ovate or broadly lanceolate, 8.5–10.5 × 2.8–4.2 mm petals, 6.5–7.5 mm long stamen with yellow anther, a 8.5–9.5 mm long, exerted style and a globose stigma. Information on ecology, phenology and preliminary conservation assessment of the proposed new species are provided. In addition, we also provide an identification key to the nine Argostemma species found in Vietnam.